Communicated Collective Knowledge: Realizing Human Potential Through Social Cognition And Information Integration Processes - Macik-Frey, Marilyn (Journal of Knowledge Management Practice, 2012)
Firms are struggling to manage knowledge, a growing source of competitive advantage. Intellectual capital often lies dormant without the needed systems and processes to realize its potential. Despite years of work in this area, organizations still struggle to find ways to harness this resource. Better strategies are needed to transform it into communicated collective knowledge that move the firm toward its goals. This paper explores knowledge management from a cross-disciplinary perspective. Borrowing from strategic management, organizational behavior, social cognition, leadership, and organizational communication theories, an inclusive model is developed. The interdependence of the organizational communication system with metacognitions, transactive memory systems (TMS) and cognition scripts provides a unique view of the process. Guidelines are provided that are suggested by the model to guide practitioners in creating efficient and effect communication systems that support the social cognitions necessary to convert dormant human knowledge into a realized asset -- collective communicated knowledge.
Keywords: Knowledge management; Social cognition; Information integration; Communicated collective knowledge